The diversity of native tree species from Bung Jagoi community forests, Bau, Sarawak and their potential for reforestation - Julia, Nelson; Tonga, Noweg; Ismail, Jusoh; Philip, Bridgette; Andrew Alek, Tuen; Stephanie, Judi (Routledge, 2022)
The study focuses on the diversity of native species from which can be selected potential species in Bung Jagoi community forests for reforestation. Multi-aged regeneration survey using nested plot design was carried out on four types of forest in Bung Jagoi community forests. The findings indicate that the intact and undisturbed primary forests are more diverse and hold a number of species with higher importance value than the disturbed forests. Bung Jagoi community forests also have abundant potential native species for reforestation.